Clinical legal education in Singapore - KOMAN, Rathna (Institutional Knowledge at Singapore Management University, 2015)
Law schools have traditionally confined themselves to the academic instruction of law, but recent curriculum development, around the world and in Singapore, represents a paradigm shift in goals and methods of instruction. Clinical legal education (CLE) programs have become an established feature of the Singapore law school curriculum, in order to, inter alia, instill legal professionalism in students and fulfill an institutional responsibility toward indigent needs.